Implementation of the Islamic Ramadan Study Program Policy in Vocational High Schools - Wahyuningsih, Yenik; Uzliva, Citra Aulia; Widyaningsih, Riza Aulia; Ghozali, Ghozali (STAI Publisistik Thawalib Jakarta, 2025)
Vocational high schools play a significant role in enhancing the quality of human resources through practical vocational education that collaborates with industry. Integrated Islamic education is necessary to instil religious values and student character. The objective is to formulate an adaptive and contextual policy model for the Islamic Ramadan Study Program in vocational high schools in order to improve religious character education and synergy among schools, communities, and families. This research is conducted through a literature review of scientific articles. The results indicate that the implementation of the Islamic Ramadan Study Program policy in vocational high schools faces challenges at each stage: problem identification, formulation, implementation, and evaluation. Policy formulation often fails to involve all stakeholders, resulting in inadequate representation. At the formulation stage, Ramadan activities have been designed; however, student participation remains low. Implementation depends on leadership and resource support, but is hindered by infrastructure and bureaucratic obstacles. Evaluation employs both test and non-test methods, yet its effectiveness is constrained by the diverse backgrounds of students and the workload of teachers. Synergy among all parties is essential for the program to operate optimally and to cultivate students' religious character. In conclusion, implementing the Islamic Ramadan Study Program in vocational high schools requires policy synergy, adequate resources, and active participation to achieve optimal effectiveness.